Perkembangan Prostitusi Online di Kota Pekanbaru Pasca Pembuburan lokalisasi Prostitusi Teleju - Mukhlis R.; Davit Rahmadan; Setia Putra (Jurnal Ilmu Hukum, 2023)
This study aims to see whether the development of online prostitution activities in Pekanbaru City after the dissolution of teleju localization and what policies will be taken by the Pekanbaru City Government in the future. The approach used is sociological legal research, by conducting searches of various existing forms of social media, and conducting in-depth interviews with various components of society, the results are then analyzed qualitatively. Pekanbaru, the capital of Riau Province, is famous for its Malay community based on traditional values coded as sara' sara' coded as Kitabullah. At the end of the late H. Herman Abdullah's tenure as mayor of Pekanbaru, there was a policy of closing the Teleju prostitution localization in Pekanbaru City. Technological developments on the one hand have a positive impact on the progress and welfare of society, especially in Pekanbaru. However, on the other hand, mobile communication technology can be misused by the public, one of which is to facilitate online prostitution transactions. Indications of online prostitution in Pekanbaru, some of the social media used are Facebook, Intragram, Twitter and Me Chatt. this is a concern for every stakeholder in Pekanbaru so that future regional legal policies are one of the efforts to prevent and deal with online prostitution activities.